A mixed-method evaluation of a New Zealand based midwifery education development unit. (July 2017) - McAra-Couper, Judith; Gilkison, Andrea; Fielder, Anna; Donald, Heather
Abstract: The Midwifery Development Education Service was established in the Birthing Unit at Middlemore Hospital in South Auckland New Zealand in 2007. The service is unique in the New Zealand midwifery context for the way it operates as a collaboration between the education and health provider to optimise the clinical learning experience of student midwives. This paper reports on the evaluation of the Midwifery Development Education Service that was undertaken in 2015. The evaluation captured the views and experience of students and midwives who had been involved with, or had worked alongside, the service. A mixed-method approach was adopted for the evaluation study, comprising of an anonymous on-line survey, qualitative interviews and focus group discussion. Considerable satisfaction with the service was identified. This article draws attention to participants' perceptions of the service as supporting student midwives; the significance of quality time in the provision of the clinical midwifery education; the situating of the service at a unique vantage point (overseeing the needs of the university and the hospital) and its impact upon the learning culture of education within the unit. A potential tension is also identified between the provision of a supportive learning environment and the assessment of student performance. Highlights: The Midwifery Development Education Service provides valuable clinical midwifery education. The service bridges the gap between university-based and hospital-based education. The service supports a culture of teaching and learning within the hospital. A tension is identified between quality education/support and student assessment.